Claudin-3在结直肠癌中的表达及意义 (Nan Fang Yi Ke Da Xue Xue Bao, 2017)
OBJECTIVE: To investigate the expression of claudin-3 in colorectal carcinoma and its association with the occurrence, progression and prognosis of colorectal cancer. METHODS: Forty surgical specimens of colorectal carcinoma and 22 adjacent normal tissues resected between October, 2010 and January, 2013 at Nanfang Hospital were examined for claudin-3 expression using immunohistochemistry, which was analyzed in association with the clinicopathological parameters and the survival of the patients. RESULTS: Claudin-3 was expressed mainly on the cell membrane, and its positivity rate was significantly higher in cancer tissues than in normal tissues (92.50% vs 59.09%, P < 0.05). In 13 cases claudin-3 expression was detected in both the cancer tissues and adjacent normal tissues with average expression scores of 4.538 and 3.269, respectively (P < 0.05). In the cancer tissues, the strongly positive expression rate was significantly higher in poorly differentiated tissues (85.71%) than in well (21.43%) and moderately (36.48%) differentiated tissues (P < 0.05), and was higher in cases with lymph node metastasis than in those without (61.11% vs 22.72%, P < 0.05). The strongly positive expression rate of claudin-3 was not correlated with the patients'age, gender, tumor location or tumor size (P>0.05). Of the 33 cancer patients followed up, 14 had a postoperative survival time no longer than 3 years and 19 had longer survival time, and their average expression scores differed significantly (4.50 vs 3.526, P < 0.05). CONCLUSION: Claudin-3 is over-expressed in colorectal cancer tissues, and its high expression may promote the occurrence and progression of colorectal cancer. Claudin-3 may serve as a molecular biomarker for early diagnosis and prognostic evaluation.